The engineering of consent: A state-of-the-art review - Abu Arqoub, Omar Ahmad; Ozad, Bahire Efe; Elega, Adeola Abdulateef (Elsevier Science Inc, 2019)
This study systematically analyzes Engineering of Consent (EOC)-focused scholarly papers published between 1947 and 2018 using content analysis and text mining. It aims to shed light on the progress of EOC research and related disciplines as well as the methodologies, data collection methods, major perspectives, and most frequent words used within these writings. Additionally, this study considers publications by region and the affiliations of first authors. The results show that only a small number of EOC-focused papers have been published since 1947; this area of public relations research has suffered from a lack of scholarly attention despite its relevance to various disciplines, and this is a situation that we hope improves. Recent trends have shown some reasons for optimism. We found that at least one EOC-focused paper has been published annually in most years since 2000 (the exceptions are 2001, 2006, 2010, 2011, and 2015). Our research shows that scholars in the fields of public relations, media studies, and political science published more papers on EOC than scholars in other fields. Research articles usually utilize qualitative research methodologies. Interviews stand out as the most widely used data collection method. Our analysis of publications by region and first-author affiliation shows that the majority of EOC papers were written by faculty and students working or studying in the United States. Seven perspectives frequently discussed by scholars and the most frequently used words within EOC papers are highlighted in a follow-up qualitative review.
Keywords: Engineering of consent (EOC); Edward Bernays; Public relations; Content analysis; Meta-analysis